Local risk indicators – Consensus report of working group 2. (3rd September 2019) - Giovannoli, Jean‐Louis; Roccuzzo, Mario; Albouy, Jean‐Pierre; Duffau, Frédéric; Lin, Guo‐Hao; Serino, Giovanni
Abstract : In implant dentistry, plaque control and oral hygiene practices are essential to limit the risk of complication and failure in the long term. All conditions around an implant in function that influence the load and pathogenicity of the microbiota are considered local risk indicators. They concern the prosthetic suprastructure design and the possibility for the patient to easily access each implant for plaque removal. Use of cemented prostheses should be limited to avoid excess cement acting as a foreign body and leading to peri‐implant disease. The crown margins should be supramucosal, and the connection should be precise to avoid a gap between the implant and the suprastructure. Every implant system is characterised by a specific design, surface texture and connection type. These features may influence peri‐implantitis development and progression, and the clinician should consider the risk of infection when selecting an implant. The soft‐tissue conditions around the implant, the width of keratinised mucosa, and the phenotype and thickness of the mucosa are also considered major risk indicators, as the presence of any mucosal defect around an implant can increase plaque accumulation and result in tissue inflammation. The pathogenicity of the microbiota around an implant is primarily dependent on pocket depth. Deep pockets around implants should be avoided and, if present, closely monitored and/or reduced. Proximity to natural teeth presenting endodontic and/or periodontal lesions may result in implant contamination, but the influence of the type of edentulism on perio‐pathogen presence is still unclear. These local conditions around an implant have a clear influence on peri‐implant diseases development and progression, but there is still only limited evidence regarding their role as true risk indicators.